Lipids in Plants and Microbes - Harwood, J. author. aut Link
X, 162 p.
Keywords: This short text is designed to provide basic information about plant and microbial lipids not only for scientists working in the microbiological and plant fields, but for anyone wanting a concise introduction to this aspect of lipid biochemistry. We have long been aware that standard biochemistry books tend to. concentrate (sometimes exclusively) on animal lipids, thus neglecting many of the important and special features of other organisms. It is not our intention that the book should be comprehensive and we have not, for instance, provided complete lists of lipid compositions of all plants and bacterial species; a number of excellent specialist texts exist and many of these are listed for further reading. Instead we have sought to provide sufficient information for an advanced undergraduate or a research student to give them a 'feel' for the subject. By a combination of generalisation and the use of examples of special interest we hope the book will whet the appetite of the reader so that, by their own research, they are stimulated to discover and, perhaps, answer some of the fascinating questions concerning plant and microbial lipids. We trust that we shall succeed in these aims, even if that will mean more competition for research funds in our own fields! J. L. HARWOOD N. J. RUSSELL November 1983 Acknowledgements Our research careers have been devoted to a study of lipids: we have no regrets and are happy to acknowledge Professors J. N.